2022
DOI: 10.3889/oamjms.2022.8073
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Optimal Time for Meals to Circadian Rhythms and Body Health (Application to Hospitality Establishments)

Abstract: Circadian rhythms, metabolism, and nutrition are closely linked, although the effects of meal timing on the human circadian system are poorly understood. The time factor biological of nature is an essential element for the functioning of cosmic systems. In the event of any defect, many problems come out as a result of this imbalance, and here came whether to change the timing of eating diets has to do with the occurrence of illness in the body and the emergence of diseases of this age such as obesity and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…The study [33] confirmed that the results of the study [34] show that there is an inverse relationship between regularity in performing aerobic exercise and the reduction of total cholesterol, as regular exercise leads to an improvement in the percentage of lipids in the blood. Low density will increase the accumulation of cholesterol in the arteries, and the higher the percentage of low-density lipids, the greater the possibility of heart disease, and the greater the percentage of excess cholesterol in the body, which is a source of danger that results in chronic diseases such as type 2 diabetes.…”
Section: Discuss the Results Of Table 4 For The Variables Of Choleste...supporting
confidence: 88%
See 1 more Smart Citation
“…The study [33] confirmed that the results of the study [34] show that there is an inverse relationship between regularity in performing aerobic exercise and the reduction of total cholesterol, as regular exercise leads to an improvement in the percentage of lipids in the blood. Low density will increase the accumulation of cholesterol in the arteries, and the higher the percentage of low-density lipids, the greater the possibility of heart disease, and the greater the percentage of excess cholesterol in the body, which is a source of danger that results in chronic diseases such as type 2 diabetes.…”
Section: Discuss the Results Of Table 4 For The Variables Of Choleste...supporting
confidence: 88%
“…A study [29] confirmed that exercise leads to a reduction in the level of low-density lipids and cholesterol in the blood, and the results of this research have been agreed from the study [21]. The training program that applied to the sample members achieved its goals in reducing the proportion of cholesterol and low-density fats [21,[33][34][35]. Shalaby et al [33] confirm that the practice of physical activity reduces levels of low-density fats, and the results of this research are consistent with the results of the study of Budiono et al [36] on a decrease in body fat percentage when exercising regularly, which leads to the prevention of blockage of arteries in the heart.…”
Section: Discuss the Results Of Table 4 For The Variables Of Choleste...supporting
confidence: 57%
“…Though, with an oral injection of NSAIDs, their clinical use is often limited due to the intestinal, gastrointestinal, and renal side effects. Dermal medication overcomes these side effects and maintains the healing level of the blood for a long time [205][206][291][292][293][294][295]. One of the disadvantages of dermal delivery is the low delivery rate due to the skin barriers.…”
Section: Dendrimers In Dermal Drug Deliverymentioning
confidence: 99%
“…In addition to the tissue toxicity, high-generation amino surfaced dendrimers also result in in ammation and activation of the complement system. As with the membrane interacting, lipid-bearing dendrimers, there is a ne balance between cytotoxicity and stimulation of cellular components of the immune system [230,249,295].…”
Section: Dendrimers For Vaccine and Immunostimulatorymentioning
confidence: 99%
See 1 more Smart Citation